Comparing The Effectiveness Of Mind Mapping And Linear Note-Taking On Block Exam Performance Of Medical Students; A Quasi-Experimental Study - Rahmi, Cut Rizka; Pratama, Muhammad Arief; Ilzana, Teuku Muhammad (Jurnal Ilmu Kedokteran dan Kesehatan, 2025)
Modern medical education demands students master a vast amount of information within a relatively short period. Effective note-taking strategies play a crucial role in the learning process and information retention. Two commonly used note-taking methods are linear notes and mind mapping. While mind mapping is claimed to enhance understanding and memory through visualization and association, its comparative effectiveness with linear notes on block exam performance among medical students still requires further exploration with strong empirical evidence. This study aims to compare the effectiveness of using mind mapping and linear note-taking on the block exam performance of medical students. This study employs a quasi-experimental design with a pre-test and post-test approach on two non-randomized groups. Participants were second-semester medical students at Universitas Imelda Medan undergoing a respiratory system block. The intervention group was trained and instructed to use mind mapping during self-study, while the control group used linear note-taking as usual. Block exam performance data were collected and statistically analyzed using comparative tests such as independent t-tests or ANOVA to control for initial confounding variables. The study found that the group utilizing mind mapping had statistically significantly higher block exam scores compared to the group using linear notes (p<0.05). Further analysis revealed improved information retention and conceptual understanding in the mind mapping group. The use of mind mapping note-taking proved more effective in improving the block exam performance of medical students compared to linear notes. These findings indicate the potential of mind mapping as a recommended learning strategy in the medical education curriculum.